Successful Penile Replantation With Cavernoglandular Shunt Procedure In Urban Setting: A Case Series - Hadibrata, Exsa; Purnomo, Awang Dyan; Tjahjo, Mars Dwi; Rivanda, Andrian; Farishal, Ahmad (Urology Journal, 2021)
Purpose: Traumatic penile amputation is a rare case with various etiologies. Penile reconstruction using replantation technique should be performed to prevent the decline of patients quality of life even in areas with limited facilites. Material and Methods: We report three cases of total penile amputation in children after circumcision, who were successfully replanted by macro-surgical technique and cavernoglandular shunt procedure. Results: Postoperative follow-up showed promising results with good micturition, erectile function, cosmetic, and minimal complications. Conclusion: Matters affecting the successful penile replantation in macro-surgical techniques have been discussed. In addition, we also highlight the potential of cavernoglandular shunt procedure that can be used as an alternative treatment for penile replantation in limited facilities.